2022
DOI: 10.1155/2022/6604984
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Profiling, and Characterization of Phytosterols and Triterpenoids from Pili (Canarium ovatum Engl.) Pulp Oil Exhibiting Antioxidant and Antibacterial Properties

Abstract: Pili (Canarium ovatum Engl.), an indigenous tree found in the Philippines, is highly regarded for its fruit due to its high economic value. During processing, the pulp is often discarded as waste but contains considerable amounts of oil and bioactive minor lipid components. The present study explored the antioxidant and antibacterial properties of saponified diethyl ether extract of pili pulp oil and related this activity to the nature of compounds present in the extract through GCMS. The extract indicated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Studies have demonstrated that neophytadiene, phytol, β-sitosterol, β-amyrone, squalene, and friedelin, isolated from various plant organs, significantly contribute to the scavenging of DPPH free radicals, hydroxyl free radicals, superoxide anions, and carbon monoxide [ 22 , 36 , 37 , 38 , 39 , 40 ]. This highlights the remarkable antioxidant properties of these compounds across a range of reactive oxygen species.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that neophytadiene, phytol, β-sitosterol, β-amyrone, squalene, and friedelin, isolated from various plant organs, significantly contribute to the scavenging of DPPH free radicals, hydroxyl free radicals, superoxide anions, and carbon monoxide [ 22 , 36 , 37 , 38 , 39 , 40 ]. This highlights the remarkable antioxidant properties of these compounds across a range of reactive oxygen species.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, mixtures of the above compounds have been shown to have diverse biological activities. Dumandan et al [66] showed that the mixture of brassicasterol, campesterol, and stigmasterol presented antimicrobial activity. Prabhakar et al [67] found that the mixture of brassicasterol, campesterol, and β-sitosterol presented activity against androgenic alopecia as they were potential inhibitors of 5α-reductase1.…”
Section: Discussionmentioning
confidence: 99%